2022
DOI: 10.2147/jpr.s359512
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Results of Percutaneous Cervical Nucleoplasty for Cervical Radicular Pain: A Retrospective Cohort Study

Abstract: Purpose Percutaneous cervical nucleoplasty (PCN) is a minimally invasive treatment for cervical radicular pain due to a disc herniation. Preliminary results show equivalent patient-reported outcomes of PCN as compared to conventional anterior cervical discectomy. However, there is a paucity of long-term outcome data. Therefore, the primary objective of this study is to investigate the long-term clinical results of PCN. Patients and Methods A retrospective analysis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, in their retrospective cohort study, Rooij et al reported that the reoperation rate of 158 patients over 41.5 months was 21.4%. They concluded that the reoperation rate was acceptable and suggested a potential role for PCN as a less invasive treatment option before ACD [ 36 ]. Our data show that 90 PCN patients were recruited in our series, and only one patient received ADR three months after PCN due to a lack of improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their retrospective cohort study, Rooij et al reported that the reoperation rate of 158 patients over 41.5 months was 21.4%. They concluded that the reoperation rate was acceptable and suggested a potential role for PCN as a less invasive treatment option before ACD [ 36 ]. Our data show that 90 PCN patients were recruited in our series, and only one patient received ADR three months after PCN due to a lack of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that PCN does not represent an alternative to PCD, ACD and ADR [ 24 ], but may be used to postpone or to decrease the need for eventual-step cervical fusion surgery to treat degenerative cervical disc disease [ 16 ]. However, it may have a potential role as a less invasive treatment option, before ACD is considered, for cervical radicular pain due to soft disc herniation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%